2019
DOI: 10.1016/j.resuscitation.2019.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Effect of smart devices on the quality of CPR training: A systematic review

Abstract: Aim of the review: Use of smart devices to provide real-time cardiopulmonary resuscitation (CPR) feedback in the context of out-of-hospital cardiac arrest (OHCA) has considerable potential for improving survival. However, the findings of previous studies evaluating the effectiveness of these devices have been conflicting. Therefore, we conducted a systematic review of the literature to assess the utility of smart devices for improving the quality of CPR during CPR training.Data sources: Thirteen electronic dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 29 publications
0
29
0
Order By: Relevance
“…CPR feedback systems using various smart devices have been studied over the past decade. A previous meta-analysis [ 23 ] included 11 such studies; three of them involved smartwatch-based feedback [ 14 , 15 , 16 ]. For example, Park showed that smartphone-based feedback did not improve the quality of CPR and that the hand pain associated with holding and operating a smartphone was a reason for complaint [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…CPR feedback systems using various smart devices have been studied over the past decade. A previous meta-analysis [ 23 ] included 11 such studies; three of them involved smartwatch-based feedback [ 14 , 15 , 16 ]. For example, Park showed that smartphone-based feedback did not improve the quality of CPR and that the hand pain associated with holding and operating a smartphone was a reason for complaint [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, these pilot programs have to be carefully evaluated because relevant factors for designing farreaching community CPR training programs are not well defined. In this context, smartphone applications might also be helpful in future CPR trainings [25][26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…For example, there is a growing body of research on automated audio-visual feedback provided by defibrillators utilised during cardiopulmonary resuscitation. Systematic reviews by Yeung et al (2009) and An et al (2019), as well as meta-analyses by Kirkbright et al (2014) and Wang et al (2020), already synthesise the evaluative evidence in this area, demonstrating that audiovisual feedback during resuscitation can result in better adherence to recommended chest compression rate and depth, as well as improved patient outcomes depending on the type of device used.…”
Section: Rationale For a Systematic Mixed Studies Reviewmentioning
confidence: 99%
“…For example, there is a growing body of research on automated audiovisual feedback provided by defibrillators utilised during cardiopulmonary resuscitation. Systematic reviews by Yeung et al (2009) and An et al (2019), as well as meta-analyses by Kirkbright et al (2014) and Wang et al (2020), already synthesise the evaluative evidence in this area, demonstrating that audiovisual feedback during resuscitation can result in better adherence to Author (year) Contribution Hysong ( 2009) (1) Audit and feedback has a modest, though significant positive effect on quality outcomes (2) Feedback seems more effective when delivered frequently in writing and with specific suggestions for improvement de Vos et al (2009) (1) Feedback seems most effective when given in combination with an education implementation strategy and/or the development of a quality improvement plan van Der Veer et al…”
Section: Rationale For a Systematic Mixed Studies Reviewmentioning
confidence: 99%